Viral Voices: Exploring Twitter as a Platform for Public Engagement in the 2022 Philippine Election - Christine B Tenorio; Yammie P. Daud; Lalevie C. Lubos (Jurnal Studi Pemerintahan)
The May 2022 Philippine national and local elections were the first to be held under a global pandemic, and social media likely shaped its outcome. Twitter overflows with many election-related conversations barely three weeks before the Philippine national and local elections. Given the physical limitations caused by the Covid-19 epidemic and the rising use of this technology by Filipinos, it was anticipated that support for social media in candidate campaign strategies would expand. This study aims to determine the pattern of relationship and interaction between Twitter users on political topics related to the election. Moreover, this study identifies the likes, dislikes, comments, opinions, or feedback about the public conversation content. In particular, Social Network Analysis (SNA) was employed to better understand how Twitter was used in public conversation during the 2022 Philippine election,. In addition, Sentiment analysis was used to understand better the online users' positive, negative, or neutral responses. The result shows similarities and differences revealed by the social networks. Results also indicated that users tend to share and seek information from reliable sources such as verified Twitter users and news websites